An Introduction to Mathematical Statistics - Bijma, Fetsje, 1977-; Vaart, A. W. van der; Jonker, Marianne (Book collections on Project MUSE., 2017)
Statistics is the science that focuses on drawing conclusions from data. To this end, collected data is modeled and analyzed using mathematical probability models. In Introduction to Statistics, key concepts from statistics are described and a mathematical basis for important statistical methods is provided. In addition, much attention is paid to the responsible application of statistical methods to data. The three most important subjects from statistics are estimators, tests, and reliability areas. Furthermore, well-known regression models, such as linear regression and analysis of variance, are discussed. Optimality of estimators and tests is also discussed in this book, as well as the selection of the most suitable model. Each chapter ends with a practical example in which described statistical methods are applied. This book is based on basic knowledge of probability theory, calculus, and linear algebra for the reader.